Dynamic expression of calretinin in embryonic and early fetal human cortex - González-Gómez, Miriam; Meyer, Gundela (Frontiers in Neuroanatomy, 2014)
Calretinin (CR) is one of the earliest neurochemical markers in human corticogenesis. In embryos from Carnegie stages (CS) 17 to 23, calbindin (CB) and CR stain opposite poles of the incipient cortex suggesting early regionalization: CB marks the neuroepithelium of the medial boundary of the cortex with the choroid plexus (cortical hem). By contrast, CR is confined to the subventricular zone (SVZ) of the lateral and caudal ganglionic eminences at the pallial-subpallial boundary (PSB, or antihem), from where CR+/Tbr1- neurons migrate toward piriform cortex and amygdala as a component of the lateral cortical stream. At CS 19, columns of CR+ cells arise in the rostral cortex, and contribute at CS 20 to the “monolayer” of horizontal Tbr1+/CR+ and GAD+ cells in the preplate. At CS 21, the “pioneer cortical plate” appears as a radial aggregation of CR+/Tbr1+ neurons, which cover the entire future neocortex and extend the first corticofugal axons. CR expression in early human corticogenesis is thus not restricted to interneurons, but is also present in the first excitatory projection neurons of the cortex. At CS 21/22, the cortical plate is established following a lateral to medial gradient, when Tbr1+/CR- neurons settle within the pioneer cortical plate, and thus separate superficial and deep pioneer neurons. CR+ pioneer neurons disappear shortly after the formation of the cortical plate. Reelin+ Cajal-Retzius cells begin to express CR around CS21 (7/8 PCW). At CS 21-23, the CR+ SVZ at the PSB is the source of CR+ interneurons migrating into the cortical SVZ. In turn, CB+ interneurons migrate from the subpallium into the intermediate zone following the fibers of the internal capsule. Early CR+ and CB+ interneurons thus have different origins and migratory routes. CR+ cell populations in the embryonic telencephalon take part in a complex sequence of events not analyzed so far in other mammalian species, which may represent a distinctive trait of the initial steps of human